Studi Perbandingan Sistem Pemangkasan Pada Budidaya Tanaman Melon (Cucumis Melo L.) - Yoseph Archilles Tangar; Julianus Jeksen; Yuyun Wahyuni (Fakultas Pertanian Universitas Ratu Samban, 2025)
Melon is a garden plant that grows naturally in the Mediterranean region, namely the border between Europe, Africa and west Asia. This research aims to determine the comparison of pruning in melon plants. This research uses a comparative method. Namely using data from field observations by comparing the diameter of melons with a system that uses pruning, consisting of 10 samples, namely 5 sample groups that use pruning and 5 sample groups that do not use pruning. The results of the data from the comparison method show that the diameter of the fruit that uses the pruning system is larger than the size of the fruit that does not use the pruning system